Augmented Reality and Virtual Reality in Arabic Speaking Skills Instruction: A Systematic Review of Pedagogical Contributions - Muhammad Fatih Budiman Putra; Octa Syakila Salsabila; Syahri Ramadhan Siregar; Idrus Afandi Akbar; Iklil Syaqifah (Alsina : Journal of Arabic Studies, 2026)
Advances in Augmented Reality (AR) and Virtual Reality (VR) have opened innovative opportunities in Arabic language learning, particularly in Arabic speaking skills (mahārat al-kalām). However, previous research remains fragmented, examining AR and VR separately without providing a comprehensive picture of their integration's impact. This study analyzes the role of AR and VR in enhancing Arabic speaking skills through a Systematic Literature Review using the PRISMA framework on 12 Scopus-indexed articles (2020–2025). The findings indicate that the integration of AR and VR significantly enhances communicative interaction and learning engagement. According to the reviewed studies, AR is effective in helping students enrich vocabulary and contextual understanding through visualization, while VR demonstrates greater effectiveness in improving speaking fluency, pronunciation accuracy, and self-confidence through immersive simulations. The combination creates a more holistic learning experience by integrating visual, auditory, and social interaction elements. However, implementation effectiveness is influenced by teacher readiness, technological infrastructure, and cost. This study identifies that AR and VR serve complementary pedagogical functions, with AR supporting vocabulary acquisition and VR enabling communicative practice. It emphasizes that effective implementation requires systematic alignment of instructional design, teacher professional development, and institutional infrastructure.